Legal Protection for Professional Athletes: The Perception of the Theory of Dignified Justice - Raharjo, Raden Suharsanto; Confido, Jimmy; Waileruny, Serlly (Journal of Law, Politic and Humanities, 2025)
This thesis explores the legal protection of professional basketball players in the Indonesian Basketball League (IBL), particularly concerning their right to transfer between clubs. It highlights the challenges faced by athletes due to IBL regulations that limit transfers to a specific period—between the end of a season and 30 days before the next begins—which contradicts general labor principles allowing employees to resign freely. The study examines two main issues: (1) legal norms on player transfers and dispute resolution based on the Manpower Law and Sports Law, and (2) the practical application of these rules in transfers both within and outside the IBL. Employing a normative-empirical method and analyzing relevant legal sources, the research finds that IBL players qualify as workers under labor law. Transfer restrictions infringe on their constitutional rights, and many do not receive lawful benefits like annual leave or severance. Legal dualism in dispute resolution creates further uncertainty for athletes.